Analysis of Biological Stress Response as the Impact of Workplace Bullying on Performance Perception - Dian Priharja Putri; Eka Rika Fitriyani; Elis Nurhayati; Linawati Linawati; Nurhaeni Nurhaeni; Siti Hasanah; Yayah Junayah; Juana Sopa; Lia Yuliawati (Postgraduate, University of Mataram, 2024)
This study aims to determine the extent to which workplace bullying is related to employees' performance perception at health centers and its impact on biological stress. The research was conducted on all employees at eight health centers in Regency X, randomly selected. Workplace bullying was measured using the Negative Acts Questionnaire Revised (NAQ-R), translated into Indonesian. Performance perception was measured using the Performance Perception Questionnaire. Biological stress was assessed through cortisol levels in saliva. Among the 240 participants, the majority (60%) rarely experienced workplace bullying, with an average score of 41.00 (SD=6.532). Most participants (67.1%) had a high perception of performance, with an average score of 67.12 (SD=9.747). Pearson's test results showed a value of 0.038 with a coefficient of -0.207, indicating a significant correlation between workplace bullying and performance perception. The findings also indicate that biological stress levels, measured through cortisol, correlate with lower performance perceptions. Workplace bullying contributes 4.285% to performance perception. This study provides preliminary evidence that workplace bullying can affect employee performance through biological stress mechanisms, highlighting the importance of interventions to reduce workplace bullying to improve employee well-being and performance